The Theoretical Evaluation of the Electropolymerization of Conjugated Compounds, Accompanied by their Electrocyclization - Романів, Людмила Вікторівна (Analytical and Bioanalytical Electrochemistry, 2018)
The theoretical evaluation of the electropolymerization of the pi-conjugated organic compounds has been given. The correspondent mathematical model has been developed and analyzed by means of linear stability theory and bifurcation analysis. It was shown that the presence of the electrochemical cyclization of conjugated compounds gives its strong impact on electropolymerization process, yielding the compounds with the possibility to enter the polymer chain as monomers. The cyclization may also be the cause of the oscillatory and monotonic instability in the system.
Keywords: Dopamine, Carbazole, Conducting polymers, Electropolymerization, Electrochemical cyclization, Stable steady-state